PTH-125 A New Lower Gastrointestinal 2-Week wait 'Direct to Test' Pathway Results in Earlier Diagnosis of Cancer. (4th June 2013) - Humphries, A; Clarke, J; Bhatnagar, G; Jenkins, I; Burling, D; Thomas-Gibson, S
Abstract : Introduction: As part of the National Awareness and Early Diagnosis Initiative (NAEDI) 1, a symptom awareness campaign for bowel cancer was piloted in the UK in 2010 and 2011. The results suggested that referrals from primary care would increase by up to 30% when extended nationally from 30 th January 2012. As a result, a new two-week wait (2WW) pathway for suspected colorectal cancer was developed at North West London Hospitals NHS Trust that aimed to decrease the projected burden on colonoscopy and triage the majority of patients direct to an appropriate diagnostic test - 'direct-to-test' (DTT), in order to reduce the time and number of appointments before cancer is diagnosed. Previously, patients were triaged to either an out-patient appointment or flexible sigmoidoscopy (FS); the new DTT pathway triaged patients to either FS, colonoscopy, CT colonography (CTC) or an out-patient appointment based on age and symptomatology. Methods: Outcome data for all patients referred via the old pathway for the months of May 2011 and January 2012, and those seen via the new DTT pathway for March 2012 and May 2012 were audited to assess clinical effectiveness. Results: There was a 33% increase in patients referred with suspected lower GI cancer following the NAEDI campaign, and this was sustained to May 2012. On the previous pathway the majority (60%) of patients were seen first in out-patients before a diagnostic test was requested, whereas over 85% of patients proceeded DTT with the new pathway. There was no significant difference in the proportion of colonic and extra-colonic cancers diagnosed between the two pathways, however more patients were diagnosed with colorectal polyps using the new pathway. Patients with cancer referred via the DTT pathway had a significantly reduced median time to diagnosis compared to those on the old pathway (10 days vs 15 days respectively, p < 0.05), and patients seen via the new DTT pathway had significantly fewer hospital appointments compared to those seen on the old pathway (1.9 vs 2.8 respectively, p < 0.0001). Conclusion: Symptom awareness campaigns increase demand for colorectal diagnostic services. We have demonstrated that a new DTT 2WW pathway for suspected colorectal cancer reduces the time to diagnosis of colonic neoplasia, whilst increasing outpatient capacity by involving fewer hospital attendances. Use of CT colonography for older patients decreases the burden on diagnostic colonoscopy, creating more targeted therapeutic endoscopy capacity. Disclosure of Interest: None Declared. Reference: Cancer Reform Strategy; Department of Health, December 2007.